Optimization of stir casting method of aluminum matrix composite (AMC) for the hardness properties by using Taguchi method - Arifin, Amir; Gunawan,; Yani, Irsyadi; Muhammad Yanis,; Pradifta, Raka (Penerbit Universiti Kebangsaan Malaysia, 2017)
Aluminum matrix composite (AMC) was fabricated using stir casting with fly ash and SiC as reinforcing materials. In this work, Taguchi optimization technique was utilized to analyze the significant contributions of stir casting parameters on the hardness properties of AMC. For this reason, stir casting was carried out by utilizing the combination of process parameters based on three-level of L9 Taguchi. The signal-to-noise (S/N) and the analysis of variance (ANOVA) were used to find the optimum levels and to indicate the impact of the process parameters on the hardness properties. The results show that some of process parameters have significant effect on the hardness, by comparing with the other three sintering factors, the composition of reinforcement materials gave the most significant effect on the hardness.